Processing Vat Polymerized Triply Periodic Minimal Surface Scaffolds of Hydroxyapatite. Issue 1 (25th October 2022) - Hoel, Cathleen A.; Peterson, Sara K.; Rose, Rachel; Telfeyan, Eric; Boyd, Linda A.; Her, Jae-Hyuk; Erno, Daniel J.; Bhushan, Chitresh; Martinez, Jessica S.; Davis, Brian M.; Duclos, Steven; Parthasarathy, Gautam
Abstract : Vat polymerization of ceramic slurries offers a means for producing triply periodic minimal surface (TPMS) structures, which are candidates for artificial trabecular bone replacement therapy. However, structures with relevant pore sizes below 500 μm and porosities above 80% push the limits of current ceramic additive manufacturing capabilities. Herein, printing and postprocessing of TPMS structures with features relevant to bone, specifically, pore sizes from 400 to 1, 265 μm, porosities over 75%, and wall thicknesses below 200 μm are addressed. The resolution of several key fundamental challenges includes: (a) adhesion to the build plate by starting the first layer with the highest surface area slice, (b) cleaning complex designs with two centrifugation cycles consistently removing 100% of residual slurry, (c) elimination of contamination from heating elements by sintering hydroxyapatite in a tube furnace, and (d) determining differences in firing shrinkage between designs to allow for targeting specified sintered dimensions. The outcome of this work enables the consistent fabrication of hydroxyapatite TPMS scaffolds (gyroid, trifurcating, clover) with high agreement between the computer‐aided design (CAD), printed, and fired designs in 5 mm cubes and cylinder with 8 mm diameter and 20 mm length. Abstract : Herein, the feasibility of printing and postprocessing three triply periodic minimal surface (TPMS) scaffolds with pore sizes from 350 to 1, 265 μm, porosities over 75%, and wall thicknesses of 125 μm are demonstrated. Key processing parameters, which include high build plate surface area, two centrifugation cleaning steps, tube furnace for contamination‐free sintering, and design‐specific firing shrinkage, are identified.